Identificação e caracterização de fungos melanizados com potencial de degradação de tolueno - Baron, Noemi Carla [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The introduction of xenobiotics compounds in the environment by human activities has become a common situation since the industrial revolution. Oil and its derivatives are the main polluters nowadays. Associated with the contaminations, a grave devastation of affected ecosystems happened and remains to these days causing unmeasured damage to nature. Searching for recovery of the homeostasis of affected local, alternatives to physical, chemical and biological removal of the contaminants have been developed. The set of techniques that aim the biological removal of organic pollutants is called bioremediation, currently accepted as the best by the scientific community, because the use of microbial metabolism results in low or no negative impact on ecosystems. The use of fungi in bioremediation is growing, among them melanized fungi form a group of particular interest. Characterized by black pigmentation of their colonies due the deposition of melanin in their cell wall, recent studies have shown its involvement in processes of hydrocarbon biodegradation, including BTEX (Benzene, Toluene, Ethylbenzene and Xylenes). Extremophilic and oligotrophic characteristics of these fungi are important aspects that corroborate with their potential use in bioremediation processes, as well as studies involving bioprospecting of new natural products, such as enzymes. After years of study our group has preserved a significant number of melanized yeasts and filamentous fungi isolated from different environmental substrates associated with hydrocarbons. From 200 selected isolates of this collection, it was sought those with the greatest potential for toluene biodegradation. The already published data on the subject based the establishment of a new proposal for screening BTEX-assimilating microfungi and to elaborate adapted bottles for chromatographic analysis of headspace. In addition, morphological and molecular identification of the 200 isolates resulted in...

A introdução de xenobióticos no ambiente por ações antrópicas é um quadro que se tornou comum principalmente desde a revolução industrial. O petróleo e seus derivados são os principais poluidores da atualidade. Associada às contaminações, uma séria devastação dos ecossistemas atingidos aconteceu e permanece até os dias de hoje sendo incontáveis os prejuízos já causados à natureza. Na busca da recuperação da homeostase de locais afetados, alternativas para a remoção física, química e biológica de contaminantes foram desenvolvidas. Ao conjunto de técnicas voltadas à remoção biológica de poluentes denominamos biorremediação, atualmente melhor aceito pela comunidade cientifica, pois a utilização do metabolismo microbiano resulta em baixo ou nenhum impacto negativo para os ecossistemas. O uso de fungos na biorremediação é crescente, dentre estes os fungos melanizados compõem um grupo de interesse particular. Caracterizados pela coloração negra de suas colônias devido à deposição de melanina em sua parede celular, estudos recentes comprovaram seu envolvimento em processos de biodegradação de hidrocarbonetos, incluindo os BTEX (Benzeno, Tolueno, Etilbenzeno e Xilenos). As características extremofílicas e o caráter oligotrófico destes fungos são aspectos importantes que corroboram seu potencial de utilização em processos de biorremediação, bem como para estudos que envolvam a bioprospecção de novos produtos naturais, como enzimas. Após anos de estudo nosso grupo preservou um número significativo de fungos filamentosos e leveduras melanizados isolados a partir de diferentes substratos ambientais associados a hidrocarbonetos. A partir deste acervo, dentre 200 isolados selecionados buscou-se aqueles com maior potencial para biodegradação de tolueno. Os dados já publicados sobre o tema embasaram o estabelecimento de uma nova proposta para triagem de microfungos assimiladores de BTEX e para a...
Keywords: Fungi; Fungos; Biologia - Classificação; Hidrocarbonetos; Biodegradação; Biorremediação